Geometry Effect Investigation on a Conical Chamber with Porous Media Boundary Condition Using Computational Fluid Dynamic (CFD) Technique - Yazid Bindar (Journal of Engineering and Technological Sciences, 2009)
The present study is an attempt to introduce  a  method for optimizing the  geometry  of  a  unit  process.  The  comprehensive  unit  process  performances are generated by a  CFD engine. The CFD engine can simulate the unit process performances  at  whatever  conditions.  Both  design  geometry  and  operating variables were used on the CFD simulation. The burden on a simplified process was taken out from CFD simulation. A complex geometry of a unit process is represented  by  a  secondary  reformer.  A  secondary  reformer  has  a  conical chamber  as a space to undergo  a  combustion reaction before entering  a  catalyst bed. This complexity is added by the boundary  on a  porous solid surface as the top surface of  the catalyst bed. The  conical  angle affects the flow pattern inside the  conical chamber  having a porous solid surface as its  base. The  conical  angle above  65° results  the  disappearing  of  the recirculation  flow.  The  inlet  distance from  the  porous  solid  surface  also  can  exhibit  different  characteristics  of recirculation  flow.  The  closer  the  distance  to  the  porous  solid  surface,  the stronger the recirculation is. The inlet velocity values have no significant effect on  the  flow  pattern.  The  introduction  of  a  solid  volume  inside  the  geometry creates distortion in the flow pattern. In the application, the inserted solid volume is equivalent to a burner. It means that the use of the burner inherently produces some problems of the flow distribution.